THU0491 Delay of Diagnosis in Still's Disease is Associated with a Chronic/Relapsing Pattern: National, Multicenter Study of 356 Patients. (23rd January 2014) - Kalyoncu, U.; Solmaz, D.; Emmungil, H.; Yazici, A.; Kasifoglu, T.; Kimyon, G.; Ayan, A.; Bes, C.; Ozmen, M.; Oner, F. A.; Erten, S.; Cagatay, Y.; et al.
Abstract : Background: Adult onset Still disease (AOSD) is a rare disease. Its management is mostly based on expert opinion. Objectives: To assess clinical features and management of AOSD in a large sample of patients. Methods: Patients from 19 centers in Turkey participated this in retrospective study. All the patients fulfilled the Yamagushi criteria for AOSD. A case report form which included clinical data, laboratory features, disease patterns, and remission and relapse rates and treatment protocols was generated and sent to the participating centers. Responsible investigators of all centers searched their local database for AOSD. Disease patterns were assessed in patients with a follow-up longer than 12 months. Results: A total of 356 patients, (210 female, 59%) with a mean (± SD) disease onset age of 31 ± 15 years and median follow-up duration of 22 (range: 0-180) months were enrolled. Of the 356 patients, remission rate after initial therapy could be assesed in 306 (85, 9%) and data regarding the last visit were available in 254 patients (71.3%). Median lead time to diagnosis was 1 (range; 0-120) month. Main clinical features were as follows: fever (96%), arthralgia (95%), rash (67%), arthritis (65%), sore throat (64%), lymphadenopathy (28%), splenomegaly (25%). Abnormal laboratory findings were leucocytosis (85%), neutrophilia >80% (68%), anemia (65%), increased AST (49%), ALT (46%) and ferritin (96.7%). Disease pattern was assessed in 230 patients [chronic 19%, relapsing-remitting 32% and monocyclic 49%]. Patients with lead time to diagnosis longer than 3 months had more frequently chronic or relapsing pattern (21.8% vs 44.3% vs 51.1%, p<0.001). Patients with chronic pattern had more joint count than those with monocyclic pattern (6.6±7.4 vs 3.1±4.2, p<0.001). Remission was achieved in 255 patients (83.3%) with the initial treatment [steroid + MTX (84/99, 87.9%), steroid + MTX + HCQ (67/80, 83.7%), medium-high dose steroid (41/54, 85.2%), steroid + HCQ (37/38, 97.3%), NSAID (4/18, 22.2%)]. Females reached remission more frequently (91% vs 72%, p<0.001). Patients under steroid treatment had a higher remission rate than those without such treatment (87.5% vs 40.7%, p<0.001). Remission could not be achieved in 51 patients (16.7%) with the initial therapy and biological therapy was given to 18 of them (35%). Relapses occurred in 74 (32%) patients during follow-up. Median duration to relapse was 18 (3-180) months. Only, 19 patients (7.5%) had active disease at the last visit. Conclusions: Monocyclic pattern was observed more frequently than reported in the literature. This may be due to the aggressive treatment protocols (steroid plus MTX and/or HCQ). Chronic/relapsing pattern seems to be associated with a longer delay in diagnosis. Early diagnosis and aggressive treatment are important for the management of AOSD. Disclosure of Interest: None Declared